Act - Miller, Kayla (Boston : Houghton Mifflin Harcourt, 2020)
"Olive is excited to start sixth grade: new teachers, new experiences, and a field trip to the big city with her best buds! But when Olive finds out that a school policy is keeping some kids from going on the trip, she decides to act. She's prepared to do whatever it takes to be heard--even if it means running against Trent and Sawyer, two of her closest friends, in the student council election! With intense campaign competition and emotions running high, can Olive make a big change and keep her friends?"--
Includes bibliographical references.
Keywords: Middle school students -- Comic books, strips, etc; Schools -- Comic books, strips, etc; School field trips -- Comic books, strips, etc; Petitions -- Comic books, strips, etc; School elections -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Middle school students -- Fiction; Schools -- Fiction; School field trips -- Fiction; Petitions -- Fiction; School elections -- Fiction; Friendship -- Fiction; Cartoons and comics; Comics (Graphic works); Graphic novels